“Do not give me cows, give me education!”. Herding life in the context of literacy practices among pastoral Buradiga (Datoga) - Bihariová, Emília (Studia Etnologiczne i Antropologiczne, 2017)
This paper charts the past and the present lifestyle of cattle herders with regard to education among the Nilotic Buradiga, with emphasis on the changes in the perception of the relationship of livestock inheritance and its substitution by formal Western education. An attempt will be made to observe the connection between the herding life and the schooling process, and how the transmission of wealth among the Datoga is changing due to the missing livestock and the growing awareness of the benefit of formal education. Moreover, the article attempts to answer the question whether formal education could constitute a suitable replacement for the missing livestock.